Data structures and algorithms in C++ - Drozdek, Adam (Australia, 2007)
The study of data structures, a fundamental component of a computer science education, serves as the foundation upon which many other computer science fields are built. Some knowledge of data structures is a must for students who wish to do work in design, implementation, testing, or maintenance of virtually any software system. The scope and presentation of material in Data Structures and Algorithms in C++ provide students with the necessary knowledge to perform such work.
Keywords: Algorithms; Data Structures--C++; Programming Languages